Natural Sciences Teachers' Views on the Quality of Instructional Leadership in Gauteng Schools - Cynthia B Malinga; Loyiso C Jita; Abiodun Adekunle Bada (STKIP Singkawang, 2022)
With the increase in demand for school-based tasks, teachers, especially natural sciences (NS) teachers, are increasingly in need of professional support and leadership that will improve their subject instruction. This paper investigates NS teachers’ perspectives on the type and quality of instructional leadership provided for NS teaching and how this leadership is adapted to implement the curriculum successfully. This study adopted a mixed methods research approach to investigate the quality of instructional leadership for NS teaching. We used a dataset of NS teachers from 243 schools. Of these, 112 teachers completed the questionnaire and 10 were interviewed and observed from six schools in the Gauteng province of South Africa. The data obtained were analyzed using descriptive statistics for the quantitative strands, while the qualitative strands were coded and interpreted into themes. The findings revealed that some of the participants were novices in the teaching of some sections of NS and thus tended to seek help from their peers because of the less than expected and inaccessible leadership provided by heads of department (HODs). This paper argues for the distribution of leadership by recognizing the contributions made by senior, leader, or master teachers to the professional development of NS teachers in general and the differential allocation of science HODs along junior and senior secondary school subjects. This paper contributes to an understanding of the function of subject leadership beyond formal positions in the South African context.